2018
DOI: 10.1161/circheartfailure.117.004228
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive Therapy Improves Both Short- and Long-Term Prognosis in Patients With Virus-Negative Nonfulminant Inflammatory Cardiomyopathy

Abstract: To conclude, this study suggests that immunosuppressive therapy in infl-CMP patients results in an improved heart transplantation-free survival as compared with standard heart failure therapy alone, underscoring the urgent need for a large prospective multicenter trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 29 publications
5
80
0
11
Order By: Relevance
“…In 2013, the ESC proposed an alternative criteria based on the inflammatory cell type determined by immunostaining defining an abnormal inflammatory infiltrate as follows: “≥14 leucocytes/mm 2 including up to 4 monocytes/mm 2 with the presence of CD3‐positive T lymphocytes ≥7 cells/mm 2 ”. Merken et al reported that immunosuppressive therapy improved the long‐term outcomes of patients with virus‐free inflammatory cardiomyopathy basically defined by this criteria.…”
Section: Diagnosis Of Chronic Myocarditismentioning
confidence: 99%
See 2 more Smart Citations
“…In 2013, the ESC proposed an alternative criteria based on the inflammatory cell type determined by immunostaining defining an abnormal inflammatory infiltrate as follows: “≥14 leucocytes/mm 2 including up to 4 monocytes/mm 2 with the presence of CD3‐positive T lymphocytes ≥7 cells/mm 2 ”. Merken et al reported that immunosuppressive therapy improved the long‐term outcomes of patients with virus‐free inflammatory cardiomyopathy basically defined by this criteria.…”
Section: Diagnosis Of Chronic Myocarditismentioning
confidence: 99%
“…Since it has been reported that ongoing viral replication has negative prognostic implications and that virus‐positive patients are less likely to respond to immunosuppression compared with patients who do not exhibit viral replication, the lack of response to immunosuppressive therapy has been explained in part by the absence of viral genome detection in early trials. The current consensus is that myocarditis patients with biopsy‐proven viral clearance by PCR may benefit from immunosuppressive agents such as predonisone and azathioprine . Large randomized trials of immunosuppressive therapies with predonisone and azathioprine targeted at virus‐negative chronic lymphocytic myocarditis are underway …”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, differences in patient selection and study design, as well as focus on LVEF as primary endpoint on relative short follow-up durations, have led to contradicting results. A recent retrospective analysis by Merken and colleagues revealed a potential beneficial effect of immunosuppression in patients with myocarditis [85]. A prospective multicenter trial using azathioprine and prednisone is currently ongoing (NCT01877746).…”
Section: Current Therapy and Future Directionsmentioning
confidence: 99%
“…There has been inconsistency in the effect of immunosuppression treatment. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] A recent systematic review 17 showed that recent two randomised controlled trials (RCTs) with a combination therapy of prednisolone plus azathioprine demonstrated improvement in LVEF. In addition, a large propensity-matched registry data has demonstrated for the first time prognostic improvement with the combination therapy.…”
Section: Introductionmentioning
confidence: 99%